GEOCHEMISTRY AND TECTONIC SETTING OF ECLOGITE PROTOLITHS FROM KECHROS COMPLEX IN EAST RHODOPE (N.E. GREECE) - Baziotis, I.; Mposkos, E. (Bulletin of the Geological Society of Greece, 2010)
Eclogites and partially amphibolitized eclogites from the metamorphic Kechros complex in East Rhodope are studied in order to provide the geodynamic framework for the origin of their protoliths. Geochemical evidence from whole rock major and trace element concentrations shows two distinct protolith groups. The low-Fe-Ti eclogites (Charakoma locality) have low-TiO2 content (<0.67 wt%), negative Nb anomalies, positive Sr anomalies, small negative Zr and Hf anomalies and variable enrichments in LILE (e.g. Rb and Ba). The REE patterns are characterized by strong LREE enrichment (LaN/YbN=5.45-5.81), HREE depletion (GdN/YbN=1.60-1.63) and HREE abundance within the range of 9-10 × chondrite. The high-Fe-Ti eclogites (Kovalo and Virsini locality) have variable Sr contents, small to moderate LILE enrichment, HREE`s similar to MORB values and absence of Nb anomalies. The REE patterns of the Kovalo and Virsini eclogites are characterized by LREE depletion and relative flat MREE HREE patterns at approximately 20-30 × chondrite concentrations. Our results suggest that the protoliths of the Low-Ti eclogites show a continental rifting tectonic environment. In contrast, the protoliths of the High-Ti eclogites indicate formation of their protoliths by partial melting in an extensional oceanic environment.